Gambaran Radiografis Restorasi Kelas II Resin Komposit Packable, Flowable dan Pasta Regular - Rosalina Tjandrawinata; Lie Hanna Davita Wibowo (Jurnal Material Kedokteran Gigi, 2016)
Polymerization shrinkage can make a gap formation between dental cavity wall and composite resin restorative materials. In radiographic film, the gap appears radiolucent, looks like secondary caries, or bonding material.The purpose of this study was to determineradiographic difference of class II restoration usingpackable, flowable, and regular paste compositeresin. The samples were12 free caries maxillary premolarwhich were extracted from orthodontic patient. Class II cavities were prepared as follows buco-palatal distance 3 mm, mesiodistal 2 mm, depth 3mm. Samples were divided into four groups. Group 1 were restored with regular pastecomposite resin, group 2 with packable compositeresin, group 3with flowable and regular pastecomposite resin, while group 4 were restored with flowable and packable composite resin. After 24 hours, the sampleswere exposed by dental x-ray.The radiolucent areabetween dental cavity wall and resin composite restoration were 0.21-0.36mm. Data wereanalyzed using one way ANOVA, followed by LSD test showed that the distance formed in group 1, 3 and 4 were not different significantly, butdifferentsignificantlywith group 2. It can be concluded that there are radiographic difference of class II restoration using packable, flowable and regular pastecomposite resin.